Prevalence of Babesia spp. and Anaplasma marginale in cattle in the municipality of Palma, MG - Paula, Marluce Aparecida Mattos; de Oliveira, Francisco Carlos Rodrigues; Junior, Orlando Augusto Melo; Teixeira, Edwards Frazão (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Paula M.A.M., Oliveira F.C.R., Melo Jr O.A. & Frazão-Teixeira E. [Prevalence of Babesia spp. and Anaplasma marginale in cattle in the municipality of Palma, MG.] Prevalência de Babesia spp. e Anaplasma marginale em bovinos no município de Palma, MG. Revista Brasileira de Medicina Veterinária, 37(4): 359-365, 2015. Laboratório de Biologia Estrutural, Instituto Oswaldo Cruz/ Fiocruz, Avenida Brasil, 4365, Manguinhos, Rio de Janeiro, RJ 21040-361, Brasil. E-mail: edwards.teixeira@ioc.fiocruz.br We verified the prevalence of hemoparasites in 40 cattle with ages varying from one month to 12 years old, in two farms of the Municipality of Palma, Minas Gerais state, Brazil. Two blood smear samples were collected from each animal: one from the tail tip and another from the ear tip. The smears were fixed, stained and observed under 100X lighted microscope magnifying glass. Twenty- -seven out of 40 animals studied (67.5%) had at least one species of hemoparasite. Among these, 21 (52.5%) were infected with Babesia spp., 10 (25%) with Anaplasma marginale and four (10%) parasitized with both hemoparasites. The studied region is potentially enzootic for the detected parasites and there is high risk for clinical cases of tick-borne disease. Both anatomic points, tail and ear tips, are good spots for blood collection and smear confection for hemoparasite investigation.